Evaluation of different blood parameters from endurance horses competing at 160 km - Ertelt, A.; Merle, R.; Stumpff, F.; Bollinger, F.; Liertz, S.; Weber, C.; Gehlen, H. (Journal of Equine Veterinary Science, 2021)
The purpose of this study was to assess a change in different blood parameters before and after a 160 km endurance race and to evaluate differences in cardiac biomarkers between horses that completed the race and horses that did not.